2001
DOI: 10.1046/j.1365-2893.2001.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Viral hepatitis and primates: historical and molecular analysis of human and nonhuman primate hepatitis A, B, and the GB‐related viruses

Abstract: The hepatitis viruses have long been assumed to be highly host-specific, with infection of other nonhuman primates occurring due to inoculation with, or exposure to, human viruses. This paradigm has slowly changed over the last 10 years, as mounting data has revealed nonhuman primate equivalents of hepatitis A virus, hepatitis B virus, and the hepatitis C-related viruses GBV-C and GBV-A. This review summarizes the historical and molecular information for each of these groups and highlights the impact of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 76 publications
0
44
0
3
Order By: Relevance
“…Antigenically, these viruses are related to human HAV yet have a significant degree of genomic heterogeneity, with four distinct simian HAVs differing not only from each other but also from all human HAV strains (Balayan, 1992). Natural cross-species transmission is primarily limited to chimpanzees and humans, although multiple species of Old World and New World monkeys can be experimentally infected (Balayan, 1992;Robertson, 2001). In macaques, natural HAV infection is usually mild or subclinical, with rare instances of severe disease and mortality (Le Bras et al, 1984;Shevtsova et al, 1987;Balayan, 1992;Lankas and Jensen, 1987).…”
Section: Hepatitis a Virus (Infectious Hepatitis)mentioning
confidence: 99%
“…Antigenically, these viruses are related to human HAV yet have a significant degree of genomic heterogeneity, with four distinct simian HAVs differing not only from each other but also from all human HAV strains (Balayan, 1992). Natural cross-species transmission is primarily limited to chimpanzees and humans, although multiple species of Old World and New World monkeys can be experimentally infected (Balayan, 1992;Robertson, 2001). In macaques, natural HAV infection is usually mild or subclinical, with rare instances of severe disease and mortality (Le Bras et al, 1984;Shevtsova et al, 1987;Balayan, 1992;Lankas and Jensen, 1987).…”
Section: Hepatitis a Virus (Infectious Hepatitis)mentioning
confidence: 99%
“…In recent years, many nonhuman primate models of viral infections have been developed to study virus-host interactions and to test the efficacy of possible vaccine candidates (9,42,45,53,54). Importantly, monkey models of simian immunodeficiency virus (SIV) infection are the best animal models available to study human immunodeficiency virus (HIV) infection and AIDS pathogenesis (48,49).…”
mentioning
confidence: 99%
“…This more variable region has been used to distinguish genotypes. Genotypes I, II, and III were found in humans, while genotypes IV, V, and VI were recovered from simians (17,20,23,29). Early investigations identified a seventh genotype (25), but recent analysis of the complete capsid genome region and complete genomes of additional isolates has indicated that genotype VII should be reclassified as genotype IIB (4,17).…”
mentioning
confidence: 99%